Five years after development of the national disability, health and rehabilitation plan for Ukraine: Achievements and challenges - Volodymyr Golyk; Oksana Syvak; Klemen Grabljevec; Piotr Tederko; Christoph Gutenbrunner; Boya Nugraha (Medical Journals Sweden, 2021)
In 2015, technical consultation to support development of the National Disability, Health and Rehabilitation Plan in Ukraine was carried out by the Rehabilitation Advisory Team of the International Society of Physical and Rehabilitation Medicine. Recommendations for actions and projects to improve rehabilitation services within the healthcare system in Ukraine were developed, proposed and implemented. The achieve-ments in the subsequent 5 years include establishing, training and enabling employment at health-care facilities for new rehabilitation professionals (physical and rehabilitation medicine physi-cians, physical therapists, occupational therapists), commencing implementation of the International Classification of Functioning, Disability and Health (ICF), and increasing rehabilitation knowledge among Ukrainian communities and decision-makers. The main challenges include inappropriate healthcare legislation for developing modern rehabilitation services, gaps in the clinical environment and quality control for training rehabilitation professionals, and the slow pace of implementation of the ICF. A gen-eral facilitator is the ongoing healthcare reform in Ukraine, especially its continuation to secondary and tertiary healthcare levels. Future high-priority activ-ities will include amendments to basic healthcare legislation, and introducing a bio-psycho-social approach for the provision of rehabilitation services at all healthcare levels and all rehabilitation treatment phases, starting with the most debilitating health conditions. It will be important to continue collaboration with European and international partners.